Associations between birth weight and glucose intolerance in adulthood among Greenlandic Inuit. (April 2019) - Rønn, Pernille Falberg; Jørgensen, Marit Eika; Smith, Lærke Steenberg; Bjerregaard, Peter; Dahl-Petersen, Inger Katrine; Larsen, Christina Viskum Lytken; Grarup, Niels; Andersen, Gregers Stig
Abstract: Aims: To examine the association between birth weight and glucose intolerance in adult Greenlandic Inuit. Methods: We examined 1429 participants aged 18–56 years from two population-based, cross-sectional studies in Greenland with information on birth weight. Oral glucose tolerance tests, anthropometric measures and ultrasound of abdominal tissue were performed. Associations of birth weight with glucose markers were analysed using linear or logistic regressions. Spline analyses were conducted to examine u-shaped associations. Adjustments were done for age, sex, birth place, family history of diabetes, genetic admixture, TBC1D4 p.Arg684Ter carrier status, BMI and visceral adipose tissue. Results: The median birthweight was 3300 g and 3.9% had type 2 diabetes, T2DM. Spline analyses indicated overall linear associations. In fully adjusted analyses, an increase in birth weight of 1 kg was associated with a change in fasting plasma glucose of −0.06 mmol/L (95%CI: −0.11, −0.01), 2-h plasma glucose of −0.16 mmol/L (95%CI: −0.35, 0.02), HOMA-IR of −5.45% (95%CI: −10.34, −0.29), insulin sensitivity index of 7.04% (95%CI: 1.88, 12.45) and a trend towards a reduced risk of hyperglycaemia and T2DM, although statistically insignificant. Conclusions: Birth weight was inversely associated with hepatic and peripheral insulin resistance independently of adult adiposity. Thus, the findings support low birth weight as a contributing factor for glucose intolerance in adult Inuit in Greenland.